2018
DOI: 10.1093/cid/ciy584
|View full text |Cite
|
Sign up to set email alerts
|

A Guide to Utilization of the Microbiology Laboratory for Diagnosis of Infectious Diseases: 2018 Update by the Infectious Diseases Society of America and the American Society for Microbiologya

Abstract: The critical nature of the microbiology laboratory in infectious disease diagnosis calls for a close, positive working relationship between the physician/advanced practice provider and the microbiologists who provide enormous value to the healthcare team. This document, developed by experts in laboratory and adult and pediatric clinical medicine, provides information on which tests are valuable and in which contexts, and on tests that add little or no value for diagnostic decisions. This document presents a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
149
0
22

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(173 citation statements)
references
References 268 publications
(259 reference statements)
2
149
0
22
Order By: Relevance
“…Guidelines for diagnosis of pneumonia by other groups can also be informative though do not always specifically apply to the SOT recipient. [75][76][77][78] A tiered approach to the diagnostic evaluation of pneumonia encompasses an initial approach, followed by a more extensive evaluation if the diagnosis remains unclear or if the patient is deteriorating. If the clinical situation is critical or if a more specific diagnosis is initially suspected, respective tests are applied and the order of diagnostic tests modified.…”
Section: Iag Nos Ti C Te S Tingmentioning
confidence: 99%
“…Guidelines for diagnosis of pneumonia by other groups can also be informative though do not always specifically apply to the SOT recipient. [75][76][77][78] A tiered approach to the diagnostic evaluation of pneumonia encompasses an initial approach, followed by a more extensive evaluation if the diagnosis remains unclear or if the patient is deteriorating. If the clinical situation is critical or if a more specific diagnosis is initially suspected, respective tests are applied and the order of diagnostic tests modified.…”
Section: Iag Nos Ti C Te S Tingmentioning
confidence: 99%
“…Furthermore, by implementing electric field assisted binding of bacteria, the detection speed decreased to 5 minutes from 45 minutes, and the detection limit reduced by 3 orders of magnitude down to 10 4 cells/ml, which is the threshold at which urinary tract infections 43,44 or bronchoalveolar lavage fluid are indicated to be disease causing. 45,46 Further reduction in detection limit below 10 3 cells/ml to meet point of care and clinical requirements 47 is desired and could be obtained by optimizing the device design, PDMS well size as well as the electric field application process. Though, increasing the device size could increase the attachment of bacteria at lower concentrations, it may also reduce the sensitivity of the devices due to non-uniformity (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The recommended blood volume of blood sampled for blood culture at different ages are, for newborns 0.5-1ml, for infants1-2ml, for 1-12 years 2-5ml and >13years 10 to 20ml. 22 In study by Hanan Ramzy Ahmed Atalla And Warda Mohamed Henedy, regarding effectiveness of structured teaching program on knowledge and practice regarding blood specimen collection among nurses, revealed that obvious improvement in parameters of strategies after blood collection to avoid complications (57.4%) followed by safety aspects during blood collection parameter (46.5%) and there is little improvement in measures to improve prominence of vein parameter (45.1%) and inspection of vein parameter (30%). 23 Thus 18(60%) participants accepted that they have collected blood culture not maintaining complete asepsis at some time in past.…”
Section: Discussionmentioning
confidence: 99%